Over a million students use our free study notes to help them with their homework
We expand the parentheses to get to the equation: 713-13isqrt(6)+7isqrt(6)-iisqrt(36) which after some further calculations equals to: 91-6isqrt(6)+sqrt(36) [We got...
This fact can be deduced several ways, and I would encourage tutees to find other methods, (such as using implicit differentiation, or the chain rule.) However one of the simplest explanations is given be...
y=2x3 - ax2 + 8x +2. If we are told that B is the stationary point of the curve, then it is at that point where the gradient of the curve is equal to 0. In order to find the gradient...
8(1-sin^2(x))+6sin(x)-6=38(1-sin^2(x))+6sin(x)-9=08sin^2(x)-6sin(x)+1=0(2sin(x)-1)(4sin(x)-1)=02sin(x)-1=0 4sin(x)-1=02sin(x)=1 4sin(x)=1sin(x)=1/2 sin(x)=1/4x=(pi)/6 , 5(pi)/6 , 0.253 , 2.89
1st we will log both sides of the equation7(x+1) = 3(x+2) becomes log7(x+1) = log3(x+2)NEXT we will use the power law which is loga (x)k=k...
←
82
83
84
85
86
→
Internet Safety
Payment Security
Cyber
Essentials